Tiger & Bunny. 1 - Sakakibara, Mizuki; Nishida, Masafumi (VIZ Media, 2013)
"Superpowered humans known as NEXT appeared in the world 45 years ago. Some of them fight crime in the city of Stern Bild while promoting their corporate sponsors on the hit show Hero TV. The people love their superheroes, even if they don't completely understand them, and not all of the NEXT use their powers for good. Veteran hero Wild Tiger has years of experience fighting crime, but his ratings have been slipping. Under orders from his new employer, Wild Tiger finds himself forced to team up with Barnaby Brooks, Jr., a rookie with an attitude. Overcoming their differences will be at least as difficult for this mismatched duo as taking down superpowered bad guys!"--P. [4] of cover.